Pathogenicity of Escherichia coli O157:H7 in the intestines of neonatal calves. - Dean-Nystrom, E A (1997)
Cattle are an important reservoir of Shiga toxin-producing enterohemorrhagic Escherichia coli (EHEC) O157:H7 strains, foodborne pathogens that cause hemorrhagic colitis and hemolytic uremic syndrome in humans. EHEC O157:H7 strains are not pathogenic in calves >3 weeks old. Our objective was to determine if EHEC O157:H7 strains are pathogenic in neonatal calves. Calves <36 h old inoculated with EHEC O157:H7 developed diarrhea and enterocolitis with attaching and effacing (A/E) lesions in both the large and small intestines by 18 h postinoculation. The severity of diarrhea and inflammation, and also the frequency and extent of A/E lesions, increased by 3 days postinoculation. We conclude that EHEC O157:H7 strains are pathogenic in neonatal calves. The neonatal calf model is relevant for studying the pathogenesis of EHEC O157:H7 infections in cattle. It should also be useful for identifying ways to reduce EHEC O157:H7 infections in cattle and thus reduce the risk of EHEC O157:H7 disease in humans.